Polycyclic aromatic hydrocarbons in Seyfert and star-forming galaxies. Issue 3 (29th October 2021) - García-Bernete, I; Rigopoulou, D; Alonso-Herrero, A; Pereira-Santaella, M; Roche, P F; Kerkeni, B
ABSTRACT: Polycyclic Aromatic Hydrocarbons (PAHs) are carbon-based molecules resulting from the union of aromatic rings and related species, which are likely responsible for strong infrared emission features. In this work, using a sample of 50 Seyfert galaxies ( D L < 100 Mpc) we compare the circumnuclear (inner kpc) PAH emission of AGN to that of a control sample of star-forming galaxies (22 luminous infrared galaxies and 30 H ii galaxies), and investigate the differences between central and extended PAH emission. Using Spitzer/InfraRed Spectrograph spectral data of Seyfert and star-forming galaxies and newly developed PAH diagnostic model grids, derived from theoretical spectra, we compare the predicted and observed PAH ratios. We find that star-forming galaxies and AGN-dominated systems are located in different regions of the PAH diagnostic diagrams. This suggests that not only are the size and charge of the PAH molecules different, but also the nature and hardness of the radiation field that excite them. We find tentative evidence that PAH ratios in AGN-dominated systems are consistent with emission from larger PAH molecules ( N c > 300–400) as well as neutral species. By subtracting the spectrum of the central source from the total, we compare the PAH emission in the central versus extended region of a small sample of AGN. In contrast to the findings for the central regions of AGN-dominated systems, the PAH ratios measured in the extended regions of both type 1 and type 2 Seyfert galaxies can be explained assuming similar PAH molecular size distribution and ionized fractions of molecules to those seen in central regions of star-forming galaxies (100 < N c < 300).